PENERAPAN STRATEGI QUICK ON THE DRAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD BABUSSALAM PEKANBARU - Rusvina, Della; Antosa, Zariul; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was carried out because still of the low social studies learning outcomes of students in a class V elementary school Babussalam Pekanbaru which were caused by teachers not yet using strategies that matched the characteristics of students and learning material. For that, researchers fix student learning outcomes by implementing a strategy Quick On The Draw . The form of this research is PTK which was conducted as much in two cycles. The research time date 7 to 22 May 2018 is located in Babussalam Elementary School with the number of students is 21 people. From the results of data analysis, there was an increase in teacher activity from cycle one by 67.43% with sufficient categories increasing to 96.29% with excellent categories. Student activities also experienced an increase from cycle one by 62.96% with a sufficient category then increasing to 96.29% with a very good category. Increased teacher and student activities have an impact on student learning outcomes which also increase from a base score of by 67.43 increasing to 82.67 with an increase in precentage of 22.60%. Based on data analysis, it is proven that if a Quick On The Draw strategy applied can improve student social studies learning outcomes.Keywords : Quick On The Draw Strategy, Social Studies Learning Outcomes